Syntactic and Pragmatic Patterns of Ellipsis in Tiktok Hook Sentences - Ima Nurhasanah; Myrna Laksman Huntley (Masyarakat Linguistik Indonesia, 2026)
This study examines ellipsis in the opening segments (hooks) of TikTok cooking videos by @devina.hermawan and its role in attracting audience attention. Using a mixed-method exploratory sequential design, 17 hooks with ellipsis from videos uploaded during school holidays (2022–2025) were analyzed, followed by a survey of 103 respondents. Ellipsis frequently occurs in declarative sentences with verbal predicates and in complex and compound-complex sentences, making hooks concise and direct. It streamlines utterances while enhancing communicative effects by providing context, emphasizing benefits, and encouraging engagement. Politeness principles, particularly the tact and generosity maxims, dominate, fostering supportive and inclusive interactions. Quantitative analysis confirms that hooks significantly influence audience attraction, though other factors also play a role. This study contributes to understanding ellipsis as a communication strategy in digital culinary content and provides practical insights for designing effective hooks.